Keterampilan Pencatatan Keuangan Menggunakan Aplikasi Akuntansi UKM Pada Pelaku UMKM Kuliner Paguyuban Jaya Mandiri Kabupaten Situbondo - Hazanah, Raudatul; Herlindawati, Dwi; Mardiyana, Lisana Oktavisanti (VALUE, 2025)
Financial Accounting is one of the important things for Micro, Small and Medium Enterprises (MSMEs) for the continuity of their business. Many entrepreneurs need financial accounting, but these entrepreneurs have not been able to carry out proper financial accounting. The purpose of this study was to determine the financial recording skills of the culinary MSME Paguyuban Jaya Mandiri, Situbondo Regency. The type of research used is the type of action research developed by Stringer. This study is divided into three stages, namely look, think, act. The research subjects were selected using the purposive sampling method and obtained 23 entrepreneurs. The primary data used in the study were obtained from the results of the pre-test, post-test and interviews. While the secondary data in this study were in the form of financial records of Paguyuban Jaya Mandiri entrepreneurs. The data analysis of this study used the Miles and Huberman model qualitative descriptive data analysis. The results of the study showed that before the financial recording skills activity was carried out, entrepreneurs had not been able to carry out financial records using the MSME Accounting Application. Meanwhile, after the financial recording skills activity was carried out, entrepreneurs had financial recording skills using the MSME Accounting Application